Dynamic Mechanical Simulation of 176 mm Pitch Compound Tooth Profile Travelling Wheel of Shearer - Kan Jinbiao (Jixie chuandong)
The engagement between travelling wheel and pin rail is non-conjugated drive,the traditional strength check method for gear is no longer applicable for travelling wheel. In the past,the finite element static mechanical simulation analysis is used for strength check of travelling wheel mostly,but the static mechanical simulation analysis can not accurately reflect the actual stress state of travelling wheel,and the calculation result is not very accurate. In order to check the strength of the 176 mm pitch compound tooth profile travelling wheel more accurately,the dynamic mechanical simulation model of 176 mm pitch compound tooth profile travelling wheel is established by Solid Edge and ANSYS software. The simulation data of contact stress and bending stress changed with time are extracted to draw curves. By comparing the simulation results and the allowable stress values of the travelling wheel materials,it is found that the 176 mm pitch compound tooth profile travelling wheel can meet the requirement of the 1 500 k N traction force of shearer. Meanwhile,the change law of contact stress and bending stress with time is summarized,which is from travelling wheel tooth entering into engagement to disengaging engagement. The engagement positions between travelling wheel and pin rail when the peak value of contact stress and bending stress occurred are obtained. A basis for the further optimization of the travelling wheel tooth curve is provided. By comparing the theoretical calculation results with the simulation results,the correctness of the simulation results is verified.